Meta-analysis of the effects of different exercise modes on cardiac function and peak oxygen uptake in patients with type 2 diabetes mellitus - Jianghua, He; Feier, Ma; Dong, Zhu; Qiuying, Li; Ya, Wen; Yan, Wang (Frontiers in Physiology, 2024)
BackgroundThe benefits of exercise for primary and secondary prevention of cardiovascular events have been reported in patients with type 2 diabetes mellitus (T2DM). However, the effects of exercise on cardiac structure and function require clarification.MethodsA literature search for clinical studies reporting on the effects of exercise on cardiac structure, cardiac function, and VO2peak in T2DM patients was conducted. PubMed, Embase, EBSCO, Web of Science, and China National Knowledge Infrastructure were systematically searched for original articles published from January 2000 to July 2023. The effect size was expressed as the mean difference (MD) or standardized mean difference (SMD) and its 95% confidence interval (CI). Subgroup analyses were performed by exercise mode (high-intensity interval training [HIIT] or moderate-intensity continuous training [MICT]) and intervention duration (>6 or ≤6 months).ResultsCompared to usual care, both HIIT and MICT significantly affected left ventricular end-diastolic volume (MD: 19.44, 95% CI: 13.72 to 25.17, p < 0.00001; I2 = 42%; MD: 13.90, 95% CI: 7.64 to 20.16, p < 0.0001; I2 = 0%), but only HIIT significantly affected left ventricular mass (MD: 17.04 g, 95% CI: 5.45 to 28.62, p = 0.004; I2 = 0%). HIIT significantly improved left ventricular ejection fraction (MD: 5.52, 95% CI: 2.31 to 8.73, p = 0.0008; I2 = 0%), as did MICT in the ≤6 months subgroup (MD: 1.36, 95% CI: 0.61 to 2.10, p = 0.0004; I2 = 0%). Neither significantly affected systolic tissue velocity. HIIT significantly improved VO2peak (MD: 8.04, 95% CI: 6.26 to 9.83, p < 0.00001; I2 = 0%), as did MICT in the ≤6 months subgroup (MD: 3.33, 95% CI: 2.39 to 4.27, p < 0.00001; I2 = 0%).ConclusionExercise significantly improved cardiac structure, systolic function, and VO2peak, but did not significantly affect diastolic function in T2DM patients. HIIT seemed to be superior to MICT at improving VO2peak and left ventricular ejection fraction in T2DM patients.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, PROSPERO registration no.: CRD4242018087376